2017
DOI: 10.5812/jjcdc.13798
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Life Skills Training on Social Communication of Clients Referring to Drug Abuse Clinics

Abstract: Background: The human society has long been challenged by the issue of drug addiction. Due to cultural reasons, beliefs based on wrong perceptions and unique geographical position, Iranian society is prone to drug addiction. The addicts usually have several problems in handling social and inter-personal communications, a fact that highlights the necessity of providing life skills training to these patients. Objectives: The study is an attempt to determine the effect of life skills training on social communicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In addition, the study of Tymes, et al [17] agreed with our study findings indicating an improvement in the children life skills behavior score post intervention compared to pre intervention. Moreover, Jahanbin et al [39] who had conducted a semi-experimental study to determine the effect of life skills training on social communication of male drug addicts who referred to Tavalod Novin Drug Clinic in Larestan, Iran. Their study findings indicated a positive significant relationship between life skills training to patients referring to drug clinics and improvement of their communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study of Tymes, et al [17] agreed with our study findings indicating an improvement in the children life skills behavior score post intervention compared to pre intervention. Moreover, Jahanbin et al [39] who had conducted a semi-experimental study to determine the effect of life skills training on social communication of male drug addicts who referred to Tavalod Novin Drug Clinic in Larestan, Iran. Their study findings indicated a positive significant relationship between life skills training to patients referring to drug clinics and improvement of their communication skills.…”
Section: Discussionmentioning
confidence: 99%